Challenges experienced by students studying medicine through English medium instruction - Alanazi, Khatmah; Curle, Samantha (Frontiers in Education, 2024)
English is increasingly being used as a medium of instruction (EMI) in many institutions for teaching academic subjects, such as physical science and medicine. Although research evidence is emerging to support the positive effects EMI has on student learning such as preparing them for professional careers and improving their English language proficiency, students also encountre challenges when studying through EMI, particularly linguistic related challenges. This study aims to investigate the challenges that medical students face when learning medicine through EMI in medical context in Saudi Arabia. To achieve this aim, a mixed-method research approach was adopted.A questionnaire was distributed to 373 students studying at four medical schools, and follow-up with semi-structured interviews with 60 students. The findings revealed that students encountered numerous challenges when studying medicine through EMI including reading medical materials, understanding lectures taught purely in English, giving presentaions and speaking fluently. Notably, these challenges were more salient in the students’ first or second years of their university studies, however dissipated as students progressed in their studies. Pedagogical implications of these findings are discussed.